Fast-Slow: the paradox in the textile-clothing-fashion scenario - Fleury, Felipe Guimarães (2021)
The objective of the article, starting from the ideological presupposes that sustains the fashion movements like fast fashion and slow fashion is to analyze the idea built around the obsolescence of fashion products under the eye of the linear and circular production systems related to the meaning of the Fast-Slow paradox. Those studies are not limited to deny fast fashion and affirm slow fashion as the possible alternative to obsolescence. According to Weber (1999), the understanding of the subjective and empirical issues of these social phenomenons leads to the preliminary interest of rethinking the structure of the textile-clothing-fashion scenario and its social and environmental organization in order to review future challenges. Yet as a theoretical base, it’s used Berlim (2015), Fletcher and Grose (2011), Kazazian (2005), Minney (2016), and Salcedo (2014) to underpin the perspectives of a possible path for the ethical act of the fashion professional in a society of consuming in the views for a transition of an economical linear model to a circular one, with bigger knowledge about the sustainable development.